ANALISIS PENGARUH CELEBRITY ENDORSER DAN PROMOSI PENJUALAN TERHADAP KEUNGGULAN MEREK SERTA PENGARUHNYA TERHADAP MINAT BELI SEPEDA MOTOR YAMAHA MIO (Studi Kasus pada Warga di Kota Semarang) - Amanda, Ligya; Mudiantono, Mudiantono (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyze the effects arising from the celebrity endorser and sales promotions on brand advantage and its influence on purchase intention from Yamaha Mio motorcycles. The variables used in this study is celebrity endorser and sales promotion as an independent variable, then the brand advantage as an intervening variable and purchase intention as the dependent variable.The sample in this study were 200 respondents that came from residents in the city of Semarang, spread from the North to the South Semarang which recognize Yamaha motorcycles. The method used is accidental sampling by distributing questionnaires to the respondents. In this study developed a theoretical model to propose five hypotheses to be tested using analysis tools Structural Equation Modeling (SEM) which is operated through a program AMOS 20.0Based on the research of data processing SEM for full model has met the criteria of goodness of fit as follows, the value of chi-square = 86.719; probability = 0.099; RMSEA = 0.033; CMIN / DF = 1.221; GFI = 0.939; AGFI = 0.910; TLI = 0.988; CFI = 0.991. With the result that it can be said that this model is feasible to be used. The results showed that the purchase intention can be improved by increasing sales promotions affect the brand advantage as a determinant of success increase purchase intention.